Response surface methodology directed modeling of the biosorption of progesterone onto acid activated Moringa oleifera seed biomass: Parameters and mechanisms - Emily Ngeno; Roselyn Ongulu; Victor Shikuku; Deo Ssentongo; Benton Otieno; Patrick Ssebugere; Francis Orata (Elsevier Ltd, 2024)
In this study, chemically activated fat-free powdered Moringa oleifera seed biomass (MOSB) was synthesized, characterized, and utilized as a cost-effective biosorbent for the abstraction of progesterone (PGT) hormone from synthetic wastewater. Natural PGT is a human steroid hormone from the progestogen family. Synthetic PGT is approved for the regulation of the menstrual cycle, aiding contraception, and is administered as a hormone replacement therapy in menopausal and post-menopausal women. PGT is an endocrine disrupting chemical (EDC) with negative health impacts on biota. The X-ray diffractogram (XRD), Scanning electron microscopy Energy-dispersive X-ray spectroscopy (SEM-EDS), and Brunauer–Emmet–Teller (BET) analyses displayed a porous, amorphous biosorbent with an elemental composition of 72.5% carbon and 22.5% oxygen and a specific surface area of 210.0 m2 g− 1 . The process variables including temperature (298–338 K), pH (2–10), contact time (10–180 min), adsorbate concentration (20–500 μg L− 1 ), and adsorbent dosage (0.1–2.0 g) were optimized using response surface methodology (RSM) to obtain the greatest efficacy of MOSB during biosorption of PGT. The optimum parameters for PGT biosorption onto MOSB were: 86.8 min, 500 μg L− 1 adsorbate concentration, 298 K, and 0.1 g adsorbent dosage. PGT removal from aqueous solutions was pH-independent. The Langmuir isotherm best fitted the equilibrium data with maximal monolayer biosorption capacity of 135.8 μg g− 1 . The biosorption rate followed the pseudo-first-order (PFO) kinetic law. The thermodynamic functions (ΔG < 0, ΔH = − 9.258 kJ mol− 1 and ΔS = +44.16 J mol− 1 ) confirmed that the biosorption of PGT onto MOSB is a spontaneous and exothermic process with increased randomness at the adsorbent surface. The biosorption mechanism was physisorption and was devoid of electrostatic interactions. The findings from this study indicate that MOSB is an inexpensive, low-carbon, and environmentally friendly biosorbent that can effectively scavenge PGT from aqueous solutions.
Keywords: Moringa oleifera seed biomass (MOSB) Progesterone; Acid-activation Biosorption